The Effect of Local Taxes and Levies on Local Own-Source Revenue (PAD) Gowa Regency - Aryati Arfah (Universitas Dharma Wacana, 2022)
The research was conducted with the aim of: (1) To determine the effect of local taxes on local revenue in Gowa Regency; (2) To determine the effect of local retribution on local revenue in Gowa Regency; (3) To determine the effect of local taxes and retribution on local revenue in Gowa Regency. The data used is secondary data. The research population is the realization of Regional Original Revenue of Gowa Regency. The sample taken is 16 budget years (2005-2020). Data collection is done through observation and documentation. The data analysis method uses the classical assumption test and multiple linear regression using the SPSS version 26.0 program. The results of this study prove that partially the variables of Regional Taxes and Levies have a positive and significant effect on Regional Original Income of Gowa Regency, while simultaneously the variables of Work Motivation, Payroll Management Information Systems, and Interpersonal Communication Skills have a positive and significant effect. Of the three independent variables, the Regional Tax variable has a dominant effect on Local Revenue of Gowa Regency.